Dialogues of diversity: examining the role of educational drama techniques in affirming diversity and supporting inclusive educational practices in primary schools. Issue 1 (2nd January 2016) - Carter, Carol; Sallis, Richard
Abstract: The aim of this article is to provide primary teachers with effective ways of engaging in drama processes to affirm diversity and to promote inclusive education in regard to cultural and linguistic diversity. It is informed by, and a response to, the 'cultural and linguistic' section within the recently revised version of the Drama Australia Equity and Diversity Guidelines to which both authors contributed. It examines some ways in which recommendations and advice provided within the document can be enacted in primary schools through the use of drama education methods, in particular dramatic storytelling and process drama. Through their work the authors have found that drama techniques and processes can be highly effective in developing understandings of cultural and linguistic diversity within primary schools. By way of illustration this paper also focuses on the findings of a recent PhD project conducted by one of the authors, which focused on the education of pre-service primary teachers in the use of drama techniques to explore cultural identities and linguistic diversity. Specifically, it examined the roles culturally specific oral arts forms, including participatory storytelling (in this instance stories from South African cultures) can play in supporting drama pedagogy and intercultural understanding of pre-service primary teacher candidates and how they can transfer this knowledge to their teaching.